Wrestling Gym in Dagestan as a Space for Masculine Socialization - Poliakov Sviatoslav (Sciendo, 2022)
The paper analyzes the process of sports gender socialization of boys and adolescents in the case of freestyle wrestling in Makhachkala, the capital of the Russian North Caucasus Republic of Dagestan. The methods and practices of educating future men in the wrestling gym are functionally related to the model of hegemonic masculinity rooted in the local gender and social order, which is under pressure from urbanization and modernization. The wrestling gym insulates students from both the "demoralizing" influence of the home environment and the marginalized scripts of masculinity associated with street life. Through training, boys and adolescents acquire a masculine habitus that can later become the basis for their careers in sports and other spheres of social life, as well as the social capital necessary for successful participation in coalition clinches. They internalize the principle of consistency in gender and age stratification and the lifestyle associated with the ideology of "muscular Islam."